IMPROVING THE BASE TRAINING OF STUDENTS OF TECHNICAL OSMS BASED ON THE INFORMATION DESIGN APPROACH - Shukurov Akmal Uktamovich (American Journals, 2023)
On the basis of the information design approach, the technical OSM should take into account the information technologies used in the analysis of strengthened cases of structures in the industry and in design projects to improve the base training of lari students.
Keywords: Information, Communication, Technology, Project, approach, Foundation, OSM, student, base, prepared, improvement, society, education, technical, modeling, training, research, component, adaptation.